The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1016/j.brainres.2006.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal 3,4-methylenedioxymethamphetamine (MDMA) exposure alters neuronal protein kinase A activity, serotonin and dopamine content, and [35S]GTPγS binding in adult rats

Abstract: Recreational use of methylenedioxymethamphetamine (MDMA) has dramatically increased among juveniles and young adults of child-bearing age, and the potential for fetal exposure has increased. For this reason, it is surprising that comparatively few studies have assessed the long-term impact of early MDMA exposure on serotonin (5-HT) and dopamine (DA) neurotransmitter systems. The purpose of this study was to determine whether repeated exposure to MDMA during the preweanling period would cause long-term changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 54 publications
2
20
0
Order By: Relevance
“…MDMA exposure induced small reductions in 5-HT in the frontal cortex and hippocampus as well as hippocampal NE 85 days after MDMA treatment. The reductions in hippocampal and frontal cortex 5-HT were also observed in a subsequent study where rats did not perform behavioral tasks (Crawford et al, 2006). In addition, a reduction of DA in the prefrontal cortex and striatum was also observed in this study.…”
Section: Biochemistrysupporting
confidence: 85%
See 1 more Smart Citation
“…MDMA exposure induced small reductions in 5-HT in the frontal cortex and hippocampus as well as hippocampal NE 85 days after MDMA treatment. The reductions in hippocampal and frontal cortex 5-HT were also observed in a subsequent study where rats did not perform behavioral tasks (Crawford et al, 2006). In addition, a reduction of DA in the prefrontal cortex and striatum was also observed in this study.…”
Section: Biochemistrysupporting
confidence: 85%
“…These results suggest that MDMA works through serotonin systems in adulthood and during development, but these show different degrees of severity. This hypothesis is further supported by the finding that neonatally MDMA-treated animals had enhanced G-protein activity after 5-HTstimulation in the hippocampus and prefrontal cortex as adults, and an increase of G-protein activity after (+)-8-OH-DPAT stimulation in the hippocampus, suggesting an increase in sensitivity of the 5-HT 1A receptor (Crawford et al, 2006). The 5-HT 1A receptor has been implicated in learning and memory and is a possible mechanism for learning and memory deficits in MDMA-treated animals (Meneses and Perez-Garcia, 2007).…”
Section: Biochemistrymentioning
confidence: 69%
“…First, recent data showed that after MDMA exposure on P11, hippocampal 5-HT levels drop sharply Schaefer et al 2006). Second, MDMA treatment from P11-20 increases 5-HT 1A receptor activity in the hippocampus (Crawford et al 2006). Third, depletion of 5-HT with the tryptophan hydroxylase inhibitor Pchlorophenylalanine from P10-20 was shown to cause deficits in the radial arm maze in adult animals (Mazer et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…In the cortex of a fully developed brain, dopaminergic and serotonergic receptors are expressed in such descending pyramidal neuronal cells, or glutamatergic or GABAergic interneurons (Barnes and Sharp 1999;Carlsson 2006). Because of the absence of serotonergic and dopaminergic nuclei in our cultures, changes in mRNA levels of serotonergic and dopaminergic receptors are not likely to be responses to altered release of dopamine or serotonin that otherwise characterize the immediate responses to MDMA, preceding the serotonin depletion observed both in adults and pups (Crawford et al 2006;Galineau et al 2005;Green et al 2003;Gudelsky and Nash 1996;Koch and Galloway 1997;Koprich et al 2003a, b;Rothman and Baumann 2003). Changes in monoaminergic mRNA levels might, instead, be indirect adaptations to alterations initiated in local glutamatergic systems considering that no changes were observed in the GABAergic system.…”
Section: Discussionmentioning
confidence: 97%
“…In addition to this, MDMA can cross the placental barrier causing infants born to mothers using MDMA during pregnancy to be at increased risk of congenital birth defects (Campbell et al 2006;Ho et al 2001;McElhatton et al 1999). Similar to adults, rat pups exposed to MDMA as embryos or shortly after birth express dopaminergic and serotonergic dysregulations in terms of decreased levels of serotonin (5HT) and dopamine, and their respective metabolites 5-HIAA and HVA, as well as reduced monoaminergic turnover (Crawford et al 2006;Galineau et al 2005;Koprich et al 2003a, b). These alterations have primarily been localized to the nucleus accumbens, hippocampus, striatum, and cortex (Koprich et al 2003a, b).…”
Section: Introductionmentioning
confidence: 99%